Exploring Environmental Factors That Drive Diel Variations in Tree Water Storage Using Wavelet Analysis - Harmon, Ryan E.; Barnard, Holly R.; Day-Lewis, Frederick D.; Mao, Deqiang; Singha, Kamini (Frontiers in Water, 2021)
Internal water storage within trees can be a critical reservoir that helps trees overcome both short- and long-duration environmental stresses. We monitored changes in internal tree water storage in a ponderosa pine using moisture probes, a dendrometer, and time-lapse electrical resistivity imaging (ERI) to investigate how patterns of in-tree water storage are affected by changes in sapflow rates, soil moisture, and meteorologic factors. ERI measurements are influenced by changes in moisture, temperature, solute concentration, and material properties; thus, to evaluate changes in moisture based on ERI, the first three factors must be considered. Measurements of xylem fluid electrical conductivity were constant in the early growing season, while inverted sapwood electrical conductivity steadily increased, suggesting that increases in electrical conductivity of the sapwood did not result from an increase xylem fluid electrical conductivity. Seasonal increases in stem electrical conductivity corresponded with seasonal increases in trunk diameter, suggesting that increased electrical conductivity may result from new growth. Changes in diel amplitudes of inverted sapwood electrical conductivity, which correspond to diel changes in sapwood moisture, indicated that tree water storage use was greatest ~4-5 days after storm events, when sapwood inverted electrical conductivity measurements suggest internal stores were high. A decrease in diel amplitudes of inverted sapwood electrical conductivity during dry periods, suggest that the ponderosa pine relied on internal water storage to supplement transpiration, but as drought conditions progressed, tree water storage contributions to transpiration decreased. Wavelet analyses indicated that lag times between inverted sapwood electrical conductivity and sapflow increased after storm events, suggesting that as soils dried reliance on internal water storage increased and the time required to refill daily deficits in internal water storage increased. Lag times peaked when soil moisture returned to pre-storm event levels and then decreased as drought progressed. Short time lags between sapflow and inverted sapwood electrical conductivity corresponded with dry conditions, when ponderosa pine are known to reduce stomatal conductance to avoid xylem cavitation. Time-lapse ERI- and wavelet-analysis results highlighted the important role internal tree water storage plays in supporting transpiration throughout the course of a day, and during periods of declining subsurface moisture.